A Privacy-preserving Opportunistic Computing Framework for Mobile-Healthcare Emergency - Mishra, Supriya; Shukla, Sohit (IJRDO -Journal of Computer Science Engineering, 2016)
Nowadays the quality of healthcare hasbeen improved gradually. However, the timeconsuming pre-hospital emergency process couldsometimes cause many regrets. Therefore, theminimization of time required for providing primarycare and consultation to patients is one of the crucialfactors when trying to improve the healthcaredelivery in emergency situations. If the EmergencyMedical Technician (EMT) can hold on signs of life ofpatients immediately when accidents happened,higher quality of healthcare could be achieved.Mobile healthcare is a new paradigm that combinesthe evolution of emerging wireless communicationsand network technologies to connect healthcareanytime and anywhere. The purpose of the study is todevelop a Mobile Emergency Healthcare InformationSystem (MEHIS). A Standard Operation Procedureof Emergency Healthcare (SOPEH) is first planned.Then, the system is developed for EMT or families ofpatients to communicate with physicians in hospitals.Users can use their 3G mobile phone to transfersymptoms and information of the situation to JSPserver which then quickly delivers information whileproviding proper emergency care at the prime time.Meanwhile, MEHIS can shorten emergencyhealthcare time and therefore enhance quality ofemergency healthcare.